Growth Pattern of Yellowfin Tuna Landed At Palabuhanratu Fishing Port, Sukabumi: Pola Pertumbuhan Tuna Sirip Kuning (Thunnus albacares) yang didaratkan di PPN Palabuhanratu, Sukabumi - Mercy Patanda; Ridwan Sala; Agnestesya Manuputty (Jurnal Pengelolaan Perikanan Tropis (Journal of Tropical Fisheries Management), 2022)
Indonesia has a wide variety of fish resources and one of them is yellowfin tuna. Tuna in Palabuhanratu is caught by Tonda and swamp tuna. Tuna is an export commodity that causes an increase in catches and requires proper management of fish resources. One of the information needed in fisheries management is the relationship between weight-length and fish condition factors. The purpose of this study is to determine growth pattern and factors of yellowfin tuna conditions landed at Palabuhanratu Fishing Port. The study was conducted in Palabuhanratu from September 2021 to January 2022. Data collection was carried out at the fish landing site at Palabuhanratu Fishing Port. The data collected in this study consisted of primary data and secondary data. Primary data consist of data on the length and weight of the fish. As many as 200 yellowfin tuna was measured their total length and weight. The total lengths of the measured tuna ranged from 30.9 - 101.9 cm. The growth pattern model analysis showed b value of 2.7. This indicates that yellowfin tuna in the study area had a negative allometric growth pattern (b<3), which explains that the length gained was faster than the weight gained. Tthe condition factor of the yellowfin tuna fish ranged from 0.70 – 1.54, with an average of 1.0. The condition factor is influenced by the availability of food because Indian Ocean is available with sufficient food because the Indian Ocean is famous for its upwelling area.